Functional Properties of Gelatin Hydrolysate from Salmon Skin (Salmo salar) - Babji, Abdul Salam; Daud, Nur Aliah; Cheng, Poh Yi (Journal of Nutritional Therapeutics, 2014)
Gelatin hydrolysate is derived from a hydrolysis of gelatin (denatured collagen) to expose the functional properties of the hydrolysate obtained. This study was carried out to determine functional properties of gelatin hydrolysate from salmon skin as influenced by the degree of enzymatic hydrolysis. Aqueous extraction of gelatin from salmon skin was done at 45oC for 60 minutes. The extracted gelatin was then hydrolysed using 1% alcalase at 54.5oC and pH 8. The functional properties determined were molecular weight, solubility, foaming capacity and stability, emulsifying activity and stability index were analysed. It was found that different time of hydrolysis (5, 15, 45 and 180 minutes) resulted in different degree of hydrolysis (DH) (10, 20, 30 and 40%, respectively). The gelatin hydrolysate at 40% DH showed the highest solubility (p<0.05). However, the foaming and emulsifying properties were the highest at 10% degree of hydrolysis (p<0.05).<s></s>